Mengurangi Resiko Banjir Pada Sungai Bruno Kediri dengan Konstruksi Bendung - Marlinto Umbu Reku; Yosef Cahyo Setianto Poernomo; Sigit Winarto; Ashabul Yamin (Jurnal Manajemen Teknologi & Teknik Sipil, 2021)
Flooding is a problem that needs to be considered because it affects all sectors. The Bruno River in Kediri Regency often experiences flooding in the rainy season, although the overflow does not reach the settlements. But already, some levees in the Bruno river broke because they could not accommodate the discharge from the Bruno river. Such characteristics have the potential to be the cause of flooding. The core of the problem arranges various flood control efforts. The development of complementary infrastructure such as Water Resources becomes the right choice to overcome the flood event. This research aims to plan Water Resources to control the flood on the Bruno river, Kediri Regency. The analysis includes hydrological analysis and hydraulic analysis. The hydrological analysis includes rainfall calculations, match tests, and flood plans, while hydraulic analysis includes the calculation of bend dimensions. Rainfall data were obtained from kanyoran rain station for the past 10 years. From the rainfall data is done calculations and compared with estimates when re-from related agencies. So, the difference in discharge is known that is used as the basis of the analysis of Water Resources planning. The results of the study obtained flood discharge of 69,20762609 m3/s. ≈ 70 m3/s with a high bend planning bend 4.3m wide 30 m. The elevation of the water level downstream of the bend is +51.56 m so that the planning results can be used as a step to reduce flooding in the Bruno river.